Малощетинковые черви, обитающие на речных раках некоторых водоемов Украины. Сообщение II. Aeolosomatidae - Бошко, Е.Г. (Вестник зоологии, 1983)
Oligochactac of the Aclosomatidac family found in crayfish gill cavity (Dnieper, Yuzhny Bug, Danube basins) and described under the name of Aelosoma markewitschi Boschko ef Paschkewitschute, 1975 arc assigned to the Hystricosoma Michaelsen, 1926 genus as a subspecies of H. chappuisi Michaclsen, 1926 — H. chappuisi markewitschi Boschko et Paschkewitschute, 1975, comb. et stat. n.